Using an open-ended socio-technical design challenge for entrepreneurship education in a first-year engineering course - DeWaters, Jan; Kotla, Bhavana (Frontiers in Education, 2023)
Engineering graduates must be prepared with sound technical knowledge and a range of 21st century competencies and professional skills such as creativity, interdisciplinary collaboration, communication, and innovation to successfully solve today's complex, global problems. Equally important is a deep appreciation of the degree to which technological solutions are situated within the context of human and natural environments. Despite calls from the National Academy of Engineering and several professional organizations to broaden engineering education to embrace these skills, most engineering programs persistently focus on the importance of technical skills. This paper describes an action research project that uses an open-ended team-based design challenge to integrate entrepreneurial-minded (EM) skill development into an interdisciplinary first-year engineering course that approaches engineering from a socio-technical perspective. The challenge was implemented in two simultaneous first-year classes (n=49), with the goal of fostering students' broad professional skills and their appreciation of the links between engineering technologies and societal context. The study used a quasi-experimental design with convenience sampling and no control group to explore students' self-perceived entrepreneurial-minded (EM) skills development. Data were collected with a retrospective questionnaire comprised of a series of 5-point Likert-type questions that asked students to assess their EM skills in all three areas of the EM framework: Exhibit Curiosity, Establish Connections, and Create Value (the "3C" framework). Results indicate that students felt they developed EM skills in all three areas of the 3C Framework, with more fully developed skills in the Establish Connections and Create Value categories. Overall, this study suggests the effectiveness of using open-ended, socio-technical engineering design challenges for developing skills that will better prepare students to work collaboratively on complex and interdisciplinary problems they will face in their professional careers.